On the Social Morphogenesis of Citizenship: A Relational Approach - Donati, Pierpaolo (SocietàMutamentoPolitica, 2016)
The paper deals with the issue of the mutations in citizenship as they emerge from the crisis of the nation-state and the speeding up of the globalization processes. Within modernity, nation-states have put peculiar socio-cultural identities and larger solidarities in deep conflict, so that no real common citizenship could be achieved. With the advent of globalization and multiculturalism, we witness the fading away of statist citizenship due to a multiplicity of factors. By resorting to the morphogenetic approach, the author tries to explain why and how a transmodern (societal) citizenship is emerging, which changes the old forms of citizenship. The new forms of citizenship stem from civil society rather than from the nation-state. New interdependences and links between ‘local’ identities and ‘broader’ solidarities are building up a post-lib/lab citizenship, based upon unprecedented relational practices in dealing with social issues. The morphogenetic processes generate di erent modalities of con guring citizenship in different contexts. From a sociological viewpoint, a new societal semantics is emerging, according to which citizenship becomes a complex of rights and duties not only of individuals but also of social groups capable of reconciling self-management practices and collective goals. The name of this new game is societal citizenship, one that promotes civil and social autonomies through which citizenship can be pursued as a relational good.